UNDERSTANDING CHINESE STRATEGY - Erdenechimeg Bor,; Zandan Tsetsgee,; Khongorzul Mijiddorj, (International Journal of Innovative Technologies in Social Science, 2025)
This paper delves into the roots of Chinese strategic culture and how it influences China's current military and foreign policy decision-making. It examines China's unique geographical position as a “fenced island” bordered by twenty countries, historical experiences of containment by major powers, and deep-rooted cultural traditions to show how these factors shape China's strategic behavior. The study explores two main paradigms in Chinese strategic culture: the Confucian-Mencius focus on defensive warfare and moral justification, and the Parabellum paradigm advocating proactive use of force.By analyzing China's “four rings” security framework, the Island Chain Strategy, and historical military interventions, the paper argues that Chinese strategic culture is a blend of defensive and opportunistic elements. It highlights how China's strategy is influenced by its concerns about territorial integrity, regional influence, and global order restructuring. Understanding this complex strategic culture is crucial for interpreting China's military modernization, regional assertiveness, and long-term geopolitical goals.The paper concludes that China's strategic behavior demonstrates strategic flexibility is maintaining a defensive stance while seizing opportunities to advance its interests when circumstances permit.